Tutoria a distância : uma reflexão acerca da epistemologia da prática docente no ensino online - Santos, Elissandra Silva (2013)
This study aimed to reflect critically on the knowledge and teaching practices for Distance Tutoring in Virtual Environment for Teaching and Learning (AVEA) under the theoretical bias of ``complex thinking´´ proposed by Edgar Morin (2002), the ``practical teaching reflective´´ discussed by Donald Schön (2000) and ``epistemology of practice teachers ´professional´ reflected by Maurice Tardif (2007). Methodologically, from my experience as Tutor Distance, lead this theoretical construct, qualitative, phenomenological approach under the subjectivist-compreensivista the philosophical perspective of the phenomenological method, presented by Spiegelberg (1971). This method allowed me to make a theoretical reflection on my teaching practice as an educational phenomenon AVEA - here shaping up as empirical educational field. Thus, it was made a ``hermeneutic effort´´ to understand the whole (tutoring distance) from the individual (my experience), through the analysis of the categories ``Tutoring Distance´´, ``Online Education´´ and ``Learning via Internet´´ in light of the major theorists who think the Mentoring and Education Online. To identify the phenomenon of interactions built in AVEA in its objective and subjective aspects, resorted to the characterization of ``phenomenon´´ made by Lofland (1971) and dimensions submitted by observational Spredley (2009). As a result, I present a critical reflection on the role of mentoring in the distance online education by proposing a set of knowledge, skills and principles to the teaching practice of teacher-tutor in order to promote the construction of collaborative learning, reflective and formative AVEA. Finally, even though science of limitations, this study intend to contribute to the discussions in the field of Epistemology in Educational Practice in Online Teaching, and highlight the importance of continuing education for Distance Mentoring seeking the quality of teaching and learning via Internet.